INVESTIGATION OF THE RELATIONSHIP BETWEEN TRADE OPENNESS AND ECONOMIC GROWTH IN THE CASE OF CHINA - Khalid, Masoud Ali; A.Ali, Khalid Hayder (International Journal of Research -GRANTHAALAYAH, 2017)
In this paper, we have investigated the relationship between trade openness and long-run economic growth over the sample period 1960–2015, utilizing ARDL model. We found evidence that trade openness is directly correlated with economic growth in the long run. Furthermore, Granger Causality tests recommended that a change in trade openness impacts the long-run of economic growth through the interaction with gross capital formation in the case of China.